A criminological reading of the concept of vulnerability: a case study of Brazilian trafficking victims - Lima De Perez, Julie (2016)
The United Nations Trafficking Protocol establishes the ‘abuse of a position of vulnerability’ as one of the means used to traffic persons. This term, however, was not properly defined, leaving it open for multiple interpretations, many of which do not focus on the well-being of the supposedly vulnerable victims. Through a case study of how (potential) Brazilian victims of trafficking are dealt with in Brazil and (to a lesser extent) outside the country, this article focuses on how ‘vulnerability’ is often interpreted as a synonym of strain which leads to deviant behavior. In this way, the concept is co-opted to enable the punishment or restraint of certain people (particularly women from developing countries) who are considered to be unsuitable to migrate